Synthesis and in-situ Mo microalloying of CuCr alloy by aluminothermic self-propagating reduction - Jin-ru Han; Zhi-he Dou; Ting-an Zhang; Wang An (Journal of Materials Research and Technology)
CuCr contact material has become the preferred contact material for vacuum interrupters, and its composition design is an effective way to improve the microstructure and properties of the alloy. Based on the process of preparing CuCr alloy by self-propagating metallurgy, in-situ microalloying of Mo in CuCr alloy by aluminothermic self-propagating reduction is proposed in this paper. It is found that the addition of Mo can effectively reduce the Gibbs mixing free energy Gm of CuCr melt and the Gibbs mixing free energy change ΔGm of melt before and after liquid phase decomposition. The decrease of Gm can reduce the temperature of liquid phase decomposition, and the decrease of ΔGm can reduce the driving force of liquid phase decomposition and inhibit the liquid phase decomposition. On this basis, homogeneous CuCr48.5Mo0.6 alloy is successfully synthesized. whose microstructure exists in the form of two phases. Mo is mainly combined with Cr in CuCr alloy, and the addition of Mo promotes the irregular development of Cr-rich alloy. Solution + aging treatment can promote the refinement of CrMo phase, and at the Cu-rich matrix is dispersed with nano-scale fine Cr precipitates, which plays a role in strengthening the second phase. Therefore, the conductivity of CuCrMo alloy is increased from 12.63 MS m−1 to 17.41 MS m−1. Based on the performance of 12 kV vacuum interrupter assembled with self-propagating CuCr contacts, it is found that compared with CuCr alloy, the insulation, chopping current and breaking performance of the interrupter are obviously improved by adding Mo.